Pelatihan Penyusunan Proposal Penelitian Tindakan Kelas (PTK) sebagai Upaya Mengembangkan Kompetensi Guru di MTsN 15 Jombang - Syarifatul Maf'ulah; Esty Saraswati Nur Hartiningrum; Safiil Maarif (Pusat Riset dan Inovasi Nasional, 2023)
This service partner is a teacher at MTsN 15 Jombang. Teachers are required to develop teacher professionalism. One way is to carry out Classroom Action Research (CAR) which aims to improve the quality of learning in the classroom and can be used to fulfill the requirements for submitting promotions in continuous professional development. However, the problems faced by partners are: partners do not really understand about CAR, how to prepare CAR proposals, and implement them. Therefore, the service team carried out training on preparing CAR proposals for teachers at MTsN 15 Jombang. The implementation method through several stages. The preparation stage includes; initial observation, carrying out licensing, coordinating with partners, and compiling training materials. The implementation phase, explaining in theory about CAR each participant experienced an increase in score from pretest to posttest, (2) at least 80% of participants received a minimum score of 80. The result of the activity was that 11 teachers of MTsN 15 Jombang participated in the training. This training begins with a pretest, then provides training, and ends with a posttest. The training was held on May 8, 2023. During the training, the volunteer explained about CAR in theory, namely related to the definitions, characteristics, objectives, CAR procedures, and the systematics of preparing CAR proposals. The training was held from 8 to 20 May 2023 namely; giving pretests, providing training materials, giving posttests, and practicing making proposals. The presentation of the material was carried out on May 8 2023, while the assistance in preparing PTK proposals was carried out from May 9 to 20 2023. The pretest and posttest results showed that the average PTK training participant's pretest score was 34.1, while the average pretest score of CAR training participants was 94.5. Based on data from the pretest and posttest results, each participant experienced an increase in score from pretest to posttest and 100% of participants received a minimum score of 80, (3) at least 50% of the participants are in the process of compiling a proposal.